2022
DOI: 10.3390/ijerph191811211
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Virtual vs. In-Person School on Children Meeting the 24-h Movement Guidelines during the COVID-19 Pandemic

Abstract: The pandemic mitigation strategy of closing schools, while necessary, may have unintentionally impacted children’s moderate-to-vigorous physical activity (MVPA), sleep, and time spent watching screens. In some locations, schools used hybrid attendance models, with some days during the week requiring in-person and others virtual attendance. This scenario offers an opportunity to evaluate the impact of attending in-person school on meeting the 24-h movement guidelines. Children (N = 690, 50% girls, K–5th) wore w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
2
1
0
Order By: Relevance
“…This suggests schools were unable to encourage physical activity by remote learning methods during stay-at-home lockdowns. This is in agreement with post-lockdown work which shows that when attending in-person schooling were more physically active compared to virtual-schooling at home 29 .…”
Section: Discussionsupporting
confidence: 90%
“…This suggests schools were unable to encourage physical activity by remote learning methods during stay-at-home lockdowns. This is in agreement with post-lockdown work which shows that when attending in-person schooling were more physically active compared to virtual-schooling at home 29 .…”
Section: Discussionsupporting
confidence: 90%
“…The average number of days per week fourth-grade children living in Texas met PA guidelines (3.6 ± 2.3 days) is difficult to compare with much of the previously published literature, as most studies simply report the proportion of children meeting PA guidelines. A previous study using accelerometer-derived data reported the proportion of days fourth-grade children met PA guidelines was 47.5% ( 43 ), which is similar to our study ([3.6/7]*100% = 51.4%). Comparing the proportion of children meeting PA guidelines proves difficult, as many studies derive this proportion by averaging PA across all measured days, which does not consider the “daily” aspect of the guideline language ( 5 – 8 ).…”
Section: Discussionsupporting
confidence: 90%
“…The COVID-19 lockdown has led to a marked decline in adherence to 24 h Movement Guidelines among children and adolescents, even if major disparities were observed [53,54]. Children who attended school in person during the pandemic were more likely to meet the 24 h Movement Guidelines, especially screen time and MVPA, in contrast to sleep [55]. The decrease in movement behaviors observed during the COVID-19 lockdown has changed and implemented new habits in youth that were kept even at the end of the lockdown.…”
Section: The 24 H Movement Guidelines Among Children and Adolescentsmentioning
confidence: 99%